INFLUENCE OF CODE SWITCHING ON MASTERY OF ENGLISH SPEAKING SKILLS IN SECONDARY SCHOOLS IN KWANZA SUB-COUNTY TRANS-NZOIA COUNTY, KENYA - , David Wafula Lwangale; Fred Misati Mochacha (IJRDO- Journal of Educational Research, 2020)
The purpose of this study was to look at the influence of code switching in the teaching of speaking skills in secondary schools in Kwanza Sub-County. The study was based on Krashen Model of affective filter hypothesis (Krashen, 1985) which states that a number of affective filter variables play a facilitative role in second language acquisition. In addition Lev Vygotsky’s social Development Theory (Crawford, 1996) which states that learning contexts play an active role in language learning. The study used descriptive survey design research. The sample was drawn from eleven secondary schools in Kwanza Sub-County. The sample size in this study consisted of eleven (11) secondary schools from a population of 36 secondary schools. They were selected through stratified random sampling. Eleven (11) principals were purposively selected to the sample and 22 teachers were randomly selected with each school giving two teachers. Teachers were also randomly drawn to serve as sample members in the study. The study found that code switching may lead to corrupting the use of English language; which could eventually lead to code mixing resulting into unstable forms like Sheng’. However, it is worth noting that secondary school students’ English language competence is still developing and their performance aspect involves code switching. Nevertheless, in using code switching in speaking to students, teachers encourage them to code switch in their conversations. This enhances communication but could undermine the mastery of English language especially in written communication. It may hamper development of the learner in expressing himself or herself in written communication. Thus code switching provides an avenue for those who cannot express themselves in one language. Ultimately, the speaker develops speaking skills in the languages involved code switching. Code switching enhances learning of speaking skills especially at secondary school level. Therefore, secondary school students will improve their speaking by use of code switching. We should keep in mind that by code switching, the development of skills of a speaking in the target language is likely to take longer that if the skills were entirely taught or learnt in the language itself. It is worth noting that, with code switching, performance in English grammar, composition and speaking skills is adversely affected. This in turn affects the general performance in academics as most examinations are set in English.